Model Peningkatan Proses Produksi Dalam Menumbuhkan Bisnis Pada Tingkat Global - Ferra Eka Ramadhani; Alfira Rosadiana (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2024)
In this research, the author wants to explain the impact of international trade on Indonesia’s economic growth. Research methods that show the characteristics of the population or phenomenon being studied. Until finally, this research method mainly focuses on explaining the object of research and answering what events or phenomena occur. In the context of a country’s economy, one of the prominent discourses is about economic growth. Although there are also other discourses about unemployment, inflation, or a simultaneous increase in the price of goods, poverty, income distribution, and so on, Economic growth is important in the context of a country’s economy because it can be one measure of the growth or achievement of that country’s economy, although it cannot be denied that there are other measures. Wijono stated that economic growth is an indicator of development progress. One thing that can be used as a driving force for growth is international trade. Salvatore stated that trade can be an engine of growth. If the extent of international trade is exports and imports, then one component or both can be a driver of growth. Tambunan stated that in the early 1980s, Indonesia established a form of export promotion policy. Thus, this policy makes exports a driving force for growth.